The optimization via response surface method for micro hydrogen gas actuator. (29th November 2019) - Li, Zhixiong; Gerdroodbary, M. Barzegar; Valipour, P.; Moradi, R.; Babazadeh, Houman
Abstract: Development of an innovative sensor for detection of hydrogen gas is essential for new applications and devices. In current article, inclusive parametric analysis has been performed to disclose the chief operative term on the performance of the micro sensor of MIKRA for the detection of the hydrogen in the mixture. The main mechanism of this micro actuator highly relies on the value of the exerted Knudsen force which occurs owing to the temperature gradient in the low-pressure region. The response surface methodology (RSM) is applied to obtain an optimized formula for the evaluation of sensor performance. Besides, analysis of variance (ANOVA) is employed to analyze the influence of individual factors on sensor formulation. This work tries to estimate the effect of major parameters such as a gap of the arm, the pressure of domain, mass fraction and temperature difference on the value of Knudsen force. Moreover, reliable correlations for the estimation of the Knudsen force are presented to determine the efficiency of the micro gas actuator in the various operating conditions. Our findings confirm that the precision of the sensor enhances as the temperature difference of the cold and hot arms as well as the hydrogen mass fractions augment in our actuator. Highlights: Optimization of micro gas sensor is done by design of experiment. The impact of significant factors for detection hydrogen by Knudsen force is revealed. Comprehensive formula for mass analysis of hydrogen in the mixture by MEMS actuator is presented. Optimum condition for high precision detection of hydrogen gas in the micro sensor is determined.